APPLICATION OF THE RASCH MODEL ON THE TEST INSTRUMENT TO ANALYZE THE PROBLEM-SOLVING ABILITY OF STUDENTS IN ACID-BASE SOLUTIONS MATERIALS - Nurkintan Aprilia; Endang Susilaningsih; Sudarmin Sudarmin; Woro Sumarni; F. Widhi Mahatmanti; Naftalina Ulik Adhelia (EDUSAINS, 2021)
APPLICATION OF THE RASCH MODEL ON THE TEST INSTRUMENT TO ANALYZE THE PROBLEM-SOLVING ABILITY OF STUDENTS IN ACID-BASE SOLUTIONS MATERIALSAbstractIn 21st century education, students are required to have high problem-solving skills. This study aims to reveal the quality of the test instrument with the Rasch model. Descriptive quantitative research is used with total of 38 students of class XI SMAN 2 Semarang became the subjects in this study. The data obtained in this study is from a combination of student response patterns on the product development diagnostic test instrument. The data analysis used was IRT Rasch. Rasch model analysis for summary statistics, item-fit, wright-map, item-measure, person-measure, person-fit dan item-DIF. The value of person reliability is 0.78(sufficient), and item reliability value is 0.8(good). Cronbach's alpha value is 0.82 (very good). Based on the analysis Rasch model, it was found that there were two students (12P and 37P) whose response patterns were not ideal. The results showed problem-solving ability profile of students in the very high category of 26%, high of 29%, average of 16%, low of 13%, and very low of 16%. The results of this study indicate that the test instrument can be used for further research in measuring student problem solving and the Rasch model contributes to teachers and schools in identifying students' abilities in more detail. AbstrakPada pendidikan abad-21, siswa dituntut harus memiliki keterampilan problem-solving yang tinggi. Penilaian keterampilan problem-solving dapat dilakukan secara online yang terintegrasi pada soal tes pengetahuan. Penelitian ini bertujuan untuk mengungkap kualitas instrumen tes dengan model Rasch. Penelitian kuantitatif deskriptif digunakan dalam penelitian ini. Total 38 siswa kelas XI SMAN 2 Semarang menjadi subjek dalam penelitian ini. Data yang diperoleh dalam penelitian ini adalah dari kombinasi pola respon jawaban siswa pada instrumen tes diagnostik produk pengembangan. Analisis data yang digunakan menggunakan Item Response Theory (IRT) model Rasch. Analisis model Rasch untuk summary statistics, item-fit, wright-map, item-measure, person-measure, person-fit dan item-DIF. Nilai person reliability didapatkan sebesar 0,78, kriteria cukup, dan nilai item reliability sebesar 0,85, kriteria bagus. Nilai alpha Cronbach sebesar 0,82, kriteria bagus sekali. Berdasarkan hasil analisis Rasch model ditemukan ada dua siswa yang pola responnya tidak ideal yaitu siswa 12P dan 37P. Hasil penelitian menunjukkan profil kemampuan problem-solving siswa dengan kategori sangat tinggi sebesar 26%, tinggi sebesar 29%, rata-rata sebesar 16%, rendah sebesar 13%, dan sangat rendah sebesar 16%. Hasil penelitian ini menunjukkan bahwa instrumen tes dapat digunakan untuk penelitian lanjutan dalam mengukur pemecahan masalah siswa dan model Rasch memberikan kontribusi kepada guru dan sekolah dalam mengidentifikasi kemampuan siswa lebih rinci